A Hundred Years of the Lithuanian Folktale Research: from the Traditional Comparativism to the Modern Methods - Šlekonytė, Jūratė (Tautosakos darbai, 2015)
This article presents a historical survey of the Lithuanian folktale research in order to summarize the research tendencies, methods, influences and review the publications launching original innovative ideas, which are the most important in the development of folkloristics. Possible directions for the future research are also charted.The European folktale research is introduced in the beginning, starting with publication of the folktales’ collections by the Brothers Grimm that had sparked off the movement of folklore collection in other countries. Further, the theories of the folktales’ origins appearing in the end of the 19th century are discussed, including the one considering folktales as remnants of the ancient beliefs, and also, the migration theory and the anthropological theory. Particular importance of the Finnish historical-geographical method is acknowledged, as having inspired the international classification of folktales. Afterwards, structuralism became especially popular, emphasizing the narrative structure of the tales. The socio-historical approach to narratives shaped a singular branch in the folktale research, focusing on the meaning of the tales, their rendering and reception in different historical, social and cultural contexts. Contextual studies of folktales also enjoy considerable popularity.The article gives a chronological survey of the Lithuanian folktale studies: starting with their appearance in the end of the 19th – beginning of the 20th century, inspired by the national movement for the independent state (mostly the comparative analysis and partly, the mythological); to the research during the interwar period in Lithuania (the spread of the historical-geographical method), its continuation in the exile (the oikotype idea by C. W. von Sydow, the semiotic analysis, the Vienna historical-geographical school) and in the soviet Lithuania (the Marxist-Leninist approach, the philological and mythological research), and finally, in the independent Lithuania (the structural semantics, the philological and mythological research, the anthropological and psychological approaches, and contextualism). Admittedly, the nature and direction of research is largely determined by the social conditions, historical and political circumstances, and certain “fashionable” methodological tendencies. It is concluded that comparative analysis and philological approach to the folktales are predominant tendencies in Lithuania; also, mythological insights are abundant. The leader of the Lithuanian folktale research is undoubtedly Bronislava Kerbelytė, who has created her own unique method of narrative analysis – the structural semantic analysis of texts, constituting the basis for her several monographs and numerous publications on folktales. The narrative piece that generated the greatest amount of studies is “Eglė, the Queen of Serpents” (The Snake as Bridegroom, ATU 425M), a fairytale typical to the Baltic cultural area and reflecting the archaic Lithuanian worldview.Finally, it is acknowledged that revisiting problematics of the folktale research is rather relevant: this involves investigation of the role and meaning of the folktales in the contemporary society, the history of their publication and problems in adapting the tales to suit the needs of the modern man.
Keywords: -